DETERMINAN PENGAJUAN PEMBIAYAAN DI LINGKUNGAN BANK PERKREDITAN RAKYAT JEMBER - Nurhayati, Nurhayati; Meirina, Petty Winda (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract: The abjective of this study is finding whether the customer has the difference between a view of the product financing they take on microfinance institutions of particularinstitution of islamic finance is based on several factors. The study population sare whole customer susefinancing services on financing bank rakyat syariah"asri" jember. Nonprobability by accidental sampling is used to determine the sample. The samples are 66 respondents. Results of this study showed that there is a difference between customer perception post editems indicated multiple variables. Based on the age factor, income, and job perception there is a difference between customers. While based on the factors of education show results yang different perception where there are currently no differences between customers. Keywords : age, income, job, education, service